2020
DOI: 10.14434/ijdl.v11i3.27663
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Interest-Based Integrated Curriculum Around Esports

Abstract: A crisis of literacy has emerged among high school students in the United States. In order to encourage students’ engagement with literacy education, there is a need for an integrated curriculum of English Language Arts (ELA). An integrated language arts curriculum would allow students to learn literacy and reading skills while engaging with a motivating context. Meanwhile, esports has grown as a worldwide culture, expanding to more than just players and spectators to include a whole ecosystem of stakeholders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…What this research means for the study of competitive collegiate esports, and the co-production of digital artifacts that occurs within this community, can also be applied to the L1 classroom. To date, although there has been a plethora of research that examines the impact and influence of videogame-based learning within traditional classrooms and teaching (Arnseth, Hanghoj, Henricksen, Misfeldt, Ramberg, & Selander, 2019;Garcia, Witte, & Dail, 2020;Gerber, Abrams, Onwuegbuzie, & Benge, 2014: Squire, 2011 very little has research exists in examining the impact and influence of esports-based curriculum in a traditional school curriculum (Lee, et. al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What this research means for the study of competitive collegiate esports, and the co-production of digital artifacts that occurs within this community, can also be applied to the L1 classroom. To date, although there has been a plethora of research that examines the impact and influence of videogame-based learning within traditional classrooms and teaching (Arnseth, Hanghoj, Henricksen, Misfeldt, Ramberg, & Selander, 2019;Garcia, Witte, & Dail, 2020;Gerber, Abrams, Onwuegbuzie, & Benge, 2014: Squire, 2011 very little has research exists in examining the impact and influence of esports-based curriculum in a traditional school curriculum (Lee, et. al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The same holds true for bringing esports-based curricular material into the L1 classroom. Although some researchers are in the beginning stages of developing esports-based curricular materials (Engerman, et al, 2018;Lee, et al, 2020), these projects are often underwritten by large grants with funds for both resources and staff to manage the development of such a curriculum. In contrast, if the power and benefit of esports literacies is to transcend traditional classroom walls, where large grants and corporate sponsorship and support are not necessary, or even available, for implementating esports-related curricular experiences, then it is important to look to methods that do not rely on financial support from vested interests.…”
Section: Discussionmentioning
confidence: 99%
“…For Massively multiplayer online game (MMOG) players, the experience usually involves shifting in different narratives inside the game, and also creating and consuming online fandom content outside the game, which both require extensive text reading and comprehension (Steinkuehler, 2007 as cited in Mills, 2015). Some educators have integrated games to a high school English Language Arts (ELA) curriculum that uses esports as an instructional tool for literacy development (Lee, Wu, Lee, Fleming, Ruben, Turner, Brown, Steinkuehler, 2020). In this curriculum, students in the 9th and 10th grade explore game design elements to understand the narrative structure, while 11th and 12th grade students dive deeper into rhetoric and writing practices through entrepreneurship and marketing simulations in esports business.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This is in spite of the fact that esports have evolved into a multi-billion dollar industry (Media, 2021 ) and demonstrated real world benefits for players (Hilvoorde and Pot, 2016 ; Wu et al, 2021 ). This popularity and perceived benefits have led to esports' recognition as an official sport (esports.net, 2021 ) and their adoption in educational contexts (Cho et al, 2019 ; Lee et al, 2020 ). Similar to traditional athletics, esports skill is highly dependent on a player's ability to learn and master gameplay mechanics (Donaldson, 2017 ; Fanfarelli, 2018 ), and thus, SRL processes are likely correlated with one's chances of becoming a successful player.…”
Section: Introductionmentioning
confidence: 99%
“…Existing work has already demonstrated that esports play can improve players' emotional regulation (Wu et al, 2021 ), fine motor skills (Toth et al, 2021 ), and academic performance (Rothwell and Shaffer, 2019 ). As such, esports have seen increased adoption as extracurricular activities in schools (Cho et al, 2019 ; Lee et al, 2020 ). If esports players are demonstrating strong SRL skills, such as reflection or goal setting, it may be that their engagement with the games themselves is teaching these skills, and this may be another benefit warranting their inclusion in schools.…”
Section: Introductionmentioning
confidence: 99%